M/M/1 Multiple Vacation Queueing Systems with Differentiated Vacations. (22nd July 2014) - Ibe, Oliver C.; Isijola, Olubukola A.
Abstract : We consider a multiple vacation queueing system in which a vacation following a busy period has a different distribution from a vacation that is taken without serving at least one customer. For ease of analysis it is assumed that the service times are exponentially distributed and the two vacation types are also exponentially distributed but with different means. The steady-state solution is obtained.